2018
DOI: 10.1159/000487935
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Lobular Mastitis: Antituberculous Treatment and Outcome in 22 Patients

Abstract: Background: Granulomatous lobular mastitis (GLM) is a rare chronic inflammatory condition of the breast. The purpose of this study was to describe antituberculous treatment of GLM and the long-term follow-up outcome. Methods: This retrospective study included 22 patients who had been histopathologically diagnosed with GLM at the Second Hospital of Shandong University from January 2011 to March 2015. Clinical characteristics, ultrasonography and mammography findings, laboratory tests, treatment regimens, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Other authors have described or presented images of histological features consistent with the CNGM pattern without appreciating the association with corynebacteria or using special stains (Gram) for the identification of GPB. Many of these cases are consequently diagnosed as IGM or chronic granulomatous mastitis 17–21…”
Section: Historical Overview and Histological Featuresmentioning
confidence: 99%
“…Other authors have described or presented images of histological features consistent with the CNGM pattern without appreciating the association with corynebacteria or using special stains (Gram) for the identification of GPB. Many of these cases are consequently diagnosed as IGM or chronic granulomatous mastitis 17–21…”
Section: Historical Overview and Histological Featuresmentioning
confidence: 99%
“…The expression of C677T and A1298C MTHFR genes were observed at different loci. The transcript sequences for C677T and A1298C MTHFR genes were as follows: Mutant type C/C and wild type C/C; mutant type C/C and heterozygous C/C; mutant type C/C and mutant type T/T; heterozygous A/C and wild type C/C; heterozygous A/C and heterozygous C/T; heterozygous A/C and mutant type T/T; wild type A/A and wild type C/C; wild type A/A and heterozygous C/T; wild type A/A and mutant type T/T[ 3 , 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many authors suggested that possible etiology of GM include breast infection with microbes, autoimmune disorders and hypeprolactinemia [2]. Uncertain etiology leads to nonoptimal treatment for GM and included watch and wait strategy, antibiotics, steroids and surgery as earliest and most widely used therapy [3][4][5][6][7][8]. In cases when GM is localized in only one part of the breast, local excision is used and radical treatment is recommended only for the most extensive forms, when all breast tissue is involved [2,3,5].…”
Section: Introductionmentioning
confidence: 99%